2011
DOI: 10.4081/reumatismo.2008.274
|View full text |Cite
|
Sign up to set email alerts
|

Distress influence in fibromyalgia

Abstract: tomatologia dolorosa con allodinia e iperalgesia, si associano altri disturbi, quale astenia, alterazioni del sonno, rigidità mattutina, e/o altre sindromi disfunzionali quali dismenorrea, colon irritabile, cefalea tensiva, dispepsia funzionale gastrica, disordine temporo-mandibolare (2). La SFp interessa maggiormente il sesso femminile, con una prevalenza nella popolazione generale che è valutata tra lo 0,3 e il 3,3% (3). Dal punto di vista patogenetico, mentre una causa muscolare non sembra essere determinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Another interesting finding is that all patients in our study reported at least one recent particularly stressful life event (bereavement, financial difficulties, etc.). A recent study found that FM patients tend to report more stressful life events than controls; the authors interestingly found that this was due to the tendency of FM patients to rate more severely mild stressful events (Stisi et al, 2008).…”
Section: The High Comorbidity Between Fm and Depression May Have Seve...mentioning
confidence: 96%
“…Another interesting finding is that all patients in our study reported at least one recent particularly stressful life event (bereavement, financial difficulties, etc.). A recent study found that FM patients tend to report more stressful life events than controls; the authors interestingly found that this was due to the tendency of FM patients to rate more severely mild stressful events (Stisi et al, 2008).…”
Section: The High Comorbidity Between Fm and Depression May Have Seve...mentioning
confidence: 96%
“…The patients assessed had a higher perception of stress, confi rming the fi ndings of other authors, who have reported an important impact of that variable on FM and the severity of its symptoms. 40 Patients with FM have shown a greater perception of stress as compared with healthy controls, 41 and a greater perception of psychological stress as compared with patients with other chronic pain types. 35 When investigating the relationship between pain and stress in patients with FM and healthy individuals, Ferreira et al 42 have found no signifi cant difference in the number of stressing events between both groups, attributing their result to the way patients cope with stress, and not only to the intensity of the events experienced.…”
Section: Figurementioning
confidence: 99%
“…9 %42 kadar›nda, tetikleyici faktör olarak kronik stres var-l›¤› belirlenmifltir. [20][21][22] Bu veriler ›fl›¤›nda, uzun ve yo¤un e¤itim program› nedeniyle stresin yüksek oldu¤u düflünülen T›p Fakültesi ö¤rencileri aras›nda FMS s›kl›¤› baflka çal›flmalarda da de¤erlendirilmifltir. Eyigör ve ark., T›p Fakültesi ö¤rencilerinde FMS prevalans›n› araflt›r-d›klar› bir çal›flmada, yafl ortalamas› 20.2±1.5 olan 306 t›p fakültesi ö¤rencisinin %2'sinde FMS saptam›fllard›r.…”
Section: Tart›flmaunclassified